A Comprehensive Systematic Review of Prevalence, Diagnosis, and Management of Internet Addiction Disorder - Anindi Putri Harjanti (International Medical Journal Corp. Ltd, 2025)
Introduction: Internet Addiction Disorder (IAD) and Internet Gaming Disorder (IGD) represent significant public mental health challenges worldwide, with varying prevalence rates across regions and populations. The absence of standardized diagnostic criteria and assessment tools has led to considerable heterogeneity in reported rates and treatment outcomes. Methods: A systematic review was conducted, screening 80 peer-reviewed studies that investigated the prevalence, diagnostic methods, and management of IAD and IGD. Studies were included based on predefined criteria focusing on validated assessment tools, human participants, and appropriate study designs. Data extraction covered study characteristics, diagnostic instruments, prevalence estimates, associated factors, and treatment efficacy. Results: Global prevalence estimates vary widely, ranging from 2.6% in Northern/Western Europe to 44.6% in Northern Africa. University students are particularly vulnerable, with a pooled prevalence of 41.84%. Significant regional and demographic variations exist, with males generally exhibiting higher prevalence, except in Gulf Cooperation Council countries where females show higher rates. Cognitive-behavioral therapy (CBT) is the most evidence-based intervention, with effect sizes ranging from g = 0.92 to 1.61, though methodological limitations and cultural specificity constrain generalizability. Discussion: The heterogeneity in prevalence is largely attributable to methodological differences, including choice of assessment tools and diagnostic criteria. Effective management requires culturally adapted, multimodal interventions, with emerging evidence supporting digital and online treatment formats. Critical gaps remain in longitudinal research, female representation, and standardized diagnostic frameworks. Conclusion: IAD/IGD is a globally prevalent condition with substantial psychosocial impacts. Future research should prioritize longitudinal designs, culturally validated tools, and inclusive sampling to improve diagnostic accuracy and treatment applicability.